Factors Influencing Customer Satisfaction in the Hospitality Industry: A Case Study of Hotel Morina Malang - Adrianto, Nathanael Abel; Pasla, Peter Remy Yosy; Widyaningrum, Santi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The tourism industry in Indonesia has shown significant growth over the years, with Malang being one of the popular destinations. Hotel Morina Malang strives to provide the best service to its guests. This study aims to analyze the influence of service quality, hotel facilities, and pricing on customer satisfaction at Hotel Morina Malang. By understanding these factors, the hotel's management can formulate effective strategies to enhance customer satisfaction and competitive positioning. A quantitative approach was used, collecting data through questionnaires from hotel guests. The results indicate that all three factors significantly impact customer satisfaction.